Rebalancing space governance: a global south perspective on outer space as a global commons - Sibsankar Palit; Sibsankar Palit; Thiago S. Dias; Thiago S. Dias; Subhajit Hazra (Frontiers in Space Technologies)
Human activities beyond Earth are increasing, encompassing military, commercial, and scientific dimensions. In such a scenario, the concept of outer space as a shared heritage of humankind faces an unprecedented pressure. Originally dominated by military applications following World War II, outer space has transformed into an arena where public and private space agencies are increasingly interested in utilizing space resources. On the one hand, the US Artemis Accords and Indian Space Policy 2023 facilitate space commercialization, which potentially compromises the global commons principle. On the other hand, pressing issues such as the proliferation of space debris, militarization tendencies, and planetary protection issues necessitate concerted and anticipatory international actions. This has resulted in a scenario where fair and equitable access to space governance for the Global South is more than just a symbolic representation. Therefore, this manuscript aims to examine space governance structures, particularly from the perspective of the Global South, where, through the analysis of structural imbalances in existing governance frameworks, we find avenues guided by the spirit of environmental law towards a more participatory engagement that guarantees outer space to remain a global commons serving all of humanity and not a projection of earthly power imbalances into space.